Pengaruh Perputaran Kas, Perputaran Persediaan, dan Perputaran Piutang terhadap Profitabilitas: (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Farmasi yang Terdaftar pada Bursa Efek Indonesia Periode 2019-2022) - Marisa Dhea Andriyani; Rachmat Arif (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to analyze the influence of cash turnover, inventory turnover, and receivables turnover on the profitability of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2022. This quantitative explanatory research uses secondary data from the financial reports of pharmaceutical companies listed on the IDX. Data analysis techniques include classical assumption tests and panel data regression to examine the relationship between the independent variables (cash turnover, inventory turnover, and receivables turnover) and the dependent variable (profitability). The results indicate that all three variables, both partially and simultaneously, have a significant effect on profitability. Efficient management of cash, inventory, and receivables contributes to higher profitability levels. This study highlights the importance of effective management of these components in improving the financial performance of companies. Limitations of the study include reliance on secondary data and a population limited to pharmaceutical companies listed on the IDX. Future research is suggested to extend the study period and consider other variables such as cost management and investment. A mixed-method approach with qualitative insights can provide deeper understanding. This study offers significant contributions to understanding how the management of cash, inventory, and receivables affects the profitability of pharmaceutical companies in Indonesia, and provides practical recommendations for companies, investors, and regulators to enhance the financial performance of the pharmaceutical sector.